SETTING DP TRANSMITTER PARAMETERS WITH ZERO SUPPRESSION METHOD ON TANKS - Arianne Gatari; Yuliarman Saragih (Jurnal Teknologika, 2023)
In industrial processes, measurement is an important variable. In industrial processes a lot must be controlled. Among them are pressure (pressure) in a pipe, flow in a pipe, temperature, and surface liquid (level) in a tank. Transmitter is used as a physical signal converter into a signal or sends signals from the transmitter device (sensor) to the controller and from the controller to the final controller. In this case, level measurement will be discussed by calculating the transmitter value to get accurate results before being installed in the field.